The Effect of PEGylation on Drugs' Pharmacokinetic Parameters; from Absorption to Excretion - Khajeei, Ali; Masoomzadeh, Salar; Gholikhani, Tooba; Javadzadeh, Yousef (Current drug delivery, 2024)
Until the drugs enter humans life, they may face problems in transportation, drug delivery, and metabolism. These problems can cause reducing drug's therapeutic effect and even increase its side effects. Together, these cases can reduce the patient's compliance with the treatment and complicate the treatment process. Much work has been done to solve or at least reduce these problems. For example, using different forms of a single drug molecule (like Citalopram and Escitalopram); slight changes in the drug's molecule like Meperidine and α-Prodine, and using carriers (like Tigerase®). PEGylation is a recently presented method that can use for many targets. Poly Ethylene Glycol or PEG is a polymer that can attach to drugs by using different methods and resulting sustained release, controlled metabolism, targeted delivery, and other cases. Although they will not necessarily lead to an increase in the effect of the drug, they will lead to the improvement of the treatment process in certain ways. In this article, the team of authors has tried to collect and carefully review the best cases based on the PEGylation of drugs that can help the readers of this article.